Involvement of autophagy and gut dysbiosis in ambient particulate matter-induced colonic inflammation - Cheng, Hsien-Jen; Hsu, Wei-Lun; Lin, Pinpin; Chen, Yu-Cheng; Lin, Tang-Huang; Fang, Shih-Shuan; Tsai, Ming-Hsien; Lin, Yen-Ju; Wang, Shuo-Ping; Chen, Hsin; Jan, Ming-Shiou; Luo, Yueh-Hsia (Ecotoxicology and environmental safety, 2024)
Ambient fine particulate matter (PM2.5), a vital environmental toxicant, not only adversely affects the cardiovascular and respiratory systems but also potentially exhibits an association with intestinal inflammation and colorectal cancer (CRC). The underlying molecular mechanisms of PM2.5 impacts on CRC are still unclear. In this study, we utilized collected ambient PM2.5 and standard reference material SRM2786 to investigate the toxic effects on the colon through in vivo chronic exposure mouse and in vitro cell culture models. We employed a chronic mouse exposure model to clarify the colonic injury and gut microbiome biomarkers. Prolonged exposure to PM2.5 via oropharyngeal aspiration led to a significant rise in colonic epithelial proliferation and reduced colon length in mice. It triggered characteristics indicative of gut microbiota dysbiosis linked to inflammatory bowel disease. The gut microbiome alternations may serve as a biomarker indicating the colonic health impacts of PM2.5 exposure. PM2.5 and SRM2786-induced cytotoxicity manifested as autophagy dysregulation-mediated abnormal proliferation, IL-8 production, p62/SQSTM1 accumulation, and lysosomal membrane damage in human colon cells WiDr and Caco-2. Both PM2.5 and SRM2786 exposures led to the accumulation of p62/SQSTM1 and compromised lysosomal membrane integrity, showing impaired autophagic flux in WiDr and Caco-2 cells. Finally, we examined the correlations between atmospheric PM2.5 data and biomarkers of colonic inflammation in human population. The serum level of IL-8 was significantly correlated with regional anthropogenic pollutants. In conclusion, our findings elucidate that ambient PM2.5 exhibits adverse effects on colon health manifested as inflammation, aberrant proliferation, and gut dysbiosis, potentially mediated through autophagy dysregulation, thereby highlighting the importance of further research on the impact of environmental pollutants on gastrointestinal health. •PM2.5 exposure increased colonic epithelial proliferation, colon shorting, and gut microbiota dysbiosis.•Gut microbiome alterations may be a potential biomarker for PM2.5 exposure's impact on colonic health.•PM2.5 induced autophagy impairment, leading to abnormal proliferation, p62 accumulation, lysosomal damage, and IL-8 release.•Serum levels of IL-8 were significantly correlated with regional anthropogenic pollutants.